Factors contributing to the development of pneumothorax and mortality in patients with COVID-19 - Ozturk, Bulent; Cakmak, Muharrem; Sizlanan, Ahmet (Bayrakol Medical Publisher, 2022)
Aim: Secondary spontaneous pneumothorax is caused by underlying lung disease, while barotraumatic pneumothorax results from mechanical ventilation. SARS-CoV2 (COVID-19) is a disease that is transmitted through droplets and affects many organs such as the lungs, brain, kidney, and liver. The lungs are the most affected organ and have the greatest influence on mortality. In SARS-CoV2 infection, progression of consolidations and expansion towards the upper lobes, the development of pleural or pericardial fluid, the development of lymphadenopathy, the presence of bronchiectasis, the development of cavitation, and pneumothorax are poor prognostic factors. In our study, we aimed to compare factors contributing to the development of pneumothorax in 29 patients who developed pneumothorax during the treatment of COVID-19 infection and follow-up.Material and Methods: Age, gender, habits, co-morbid diseases, clinical, radiological, laboratory, treatment, mortality and morbidity results of 29 patients who developed pneumothorax during the treatment and follow-up of COVID-19 infection were evaluated. Patients were divided into two groups as deceased (Group1) and surviving (Group 2) patients. The results of the groups were compared.Results: We found that mean age, lymphocyte elevation, mechanical ventilator applications, length of stay in the intensive care unit, and complication development after thoracostomy were more significant in Group 1 than in Group 2 (p<0.05), whereas gender, pneumothorax localization, blood group, Rh differences, and smoking were not significant (p>0.05).Discussion: Although the number and ratio of the comparison criteria included in the study were in favor of Group 1, certain parameters were statistically significant. However, the development of pneumothorax is an important cause of mortality in SARS-CoV2 patients.
Keywords: Pneumothorax; Respiratory System; SARS-CoV2